2:0 for the Good Guys: Character Information Influences Emotion Perception - Lindeberg, S.; Craig, Belinda; Lipp, Ottmar (American Psychological Association, 2018)
Previous research has demonstrated that facial social category cues influence emotion perception such that happy expressions are categorized faster than negative expressions on faces belonging to positively evaluated social groups. We examined whether character information that is experimentally manipulated can also influence emotion perception. Across two experiments, participants learned to associate individuals posing neutral expressions with positive or negative acts. In a subsequent task, participants categorized happy and angry expressions of these same individuals as quickly and accurately as possible. As predicted, a larger happy face advantage emerged for individuals associated with positive character information than for individuals associated with negative character information. These results demonstrate that experimentally manipulated evaluations of an individual's character are available quickly and affect early stages of face processing. Emotion perception is not only influenced by preexisting attitudes based on facial attributes, but also by information about a person that has been recently acquired.